2018
DOI: 10.1016/j.watres.2017.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic degradation and environmental toxicity of ibuprofen: Roles of mineral particles and solar radiation

Abstract: The growing medical and personal needs of human populations have escalated release of pharmaceuticals and personal care products into our natural environment. This work investigates abiotic degradation pathways of a particular PPCP, ibuprofen, in the presence of a major mineral component of soil (kaolinite clay), as well as the health effects of the primary compound and its degradation products. Results from these studies showed that the rate and extent of ibuprofen degradation is greatly influenced by the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 46 publications
(50 reference statements)
3
34
0
Order By: Relevance
“…After the adsorption of ibuprofen, we found that the peak corresponding to (Fe, Si)-OH/C-O-C had shifted, which was related to the formation of hydrogen bonds between the -OH groups of inorganic materials on the MAP and the -COOH groups of ibuprofen. This finding was consistent with other reports, in which hydrogen bonding was considered the interaction between PPCPs and adsorbents [34][35][36][37][38] . www.nature.com/scientificreports www.nature.com/scientificreports/ Adsorption isotherms.…”
Section: Resultssupporting
confidence: 93%
“…After the adsorption of ibuprofen, we found that the peak corresponding to (Fe, Si)-OH/C-O-C had shifted, which was related to the formation of hydrogen bonds between the -OH groups of inorganic materials on the MAP and the -COOH groups of ibuprofen. This finding was consistent with other reports, in which hydrogen bonding was considered the interaction between PPCPs and adsorbents [34][35][36][37][38] . www.nature.com/scientificreports www.nature.com/scientificreports/ Adsorption isotherms.…”
Section: Resultssupporting
confidence: 93%
“…IBU, at 71–89 mg/L, inhibited growth of Chlorella vulgaris by 50% (48–96 h) [104], and at ≥0.1 g/L (0.5 mM), caused death of almost 100% Chlorella sp. cells [126]. For Desmodesmus subspicatus, IBU at 92 mg/L caused 50% inhibition in photosynthetic activity [84], and at 0.34 g/L, caused 50% inhibition in growth [127].…”
Section: Inhibitory Effect Of Pharmaceuticals and Personal Care Prmentioning
confidence: 99%
“…Potassium indigo tri-sulfonate (C 16 H 7 K 3 N 2 O 11 S 3 , MW: 616.72 g/mol, CAS number: 67627-18-3) was provided from Sigma-Aldrich (USA), sodium phosphate monobasic (H 2 NaO 4 P, MW: 119.98 g/mol, CAS number: 7558-80-7) was provided from Sigma life science (Germany). Orto-phosphoric acid was used for the determination of soluble ozone in the aqueous samples [33]. Ethanol (C 2 H 6 O, MW: 46.06 g/mol, CAS number: 64-17-5, >96% purity) was obtained from Altia (Finland).…”
Section: Chemicalsmentioning
confidence: 99%
“…Nevertheless, the controversial issue of this method was the toxicity of the chlorinated by-products [32]. The abiotic degradation of IBU and toxic impacts of basic ibuprofen and its secondary residues reveals the various grade of toxicity of these pharmaceuticals [33]. Accordingly, it is very urgent to discover a practically applicable method for removing IBU without or with a small amount of disinfectants or hazardous by-products.…”
Section: Introductionmentioning
confidence: 99%